Pengaruh Direct Instruction Model Terhadap Kemampuan Teknik Dasar Passing Permainan Sepak Bola Siswa Sekolah Menengah Atas - Bayu Segara Wicaksana; Ega Rahayu (Jurnal Ilmiah Wahana Pendidikan, 2022)
The learning model is very important in supporting success in achieving learning objectives, so this study aims to increase the football passing ability of the students of SMAN 1 Telukjambe Barat, because there are still many who practice soccer passing techniques with origin or not optimal. This study adopted a set of experimental methods. designed before and after testing. The data collection carried out in this study used a football passing test. The subjects of this study were 28 high school students consisting of 6 students and 22 students. This can be seen from the implementation of the research that the final test is better than the initial test in changing the pretest and posttest. It can be concluded that the direct instruction model method is useful for learning football passing skills and techniques. This level affects the basic football passing ability of students as a whole including in the good category, so that the Direct Instruction learning model can be applied in soccer learning.